2015
DOI: 10.1080/02640414.2015.1026379
|View full text |Cite
|
Sign up to set email alerts
|

Variability of performance during a 60-min running race

Abstract: The aim of the present study was to examine the variability of 1-h running performance outside the laboratory, under conditions simulating those of a real competitive event. Twenty-three male recreational runners performed on 3 occasions a 60-min simulated running race attempting to cover as long distance as possible. The races took place in an indoor track, in order to ensure stable environmental conditions. There was no difference in the distance covered between races (12,546.3 ± 217 m, 12,576 ± 219.1 m, 12,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…On average, the IMW warm-up resulted in a ;21-second (2.8%) improvement in 3,200-m performance compared with CON. The effect is similar to those in comparable studies using a variety of performance tests (25,27,36,40), and greater than the smallest worthwhile change in performance athletes show between competitions, which is about half the typical variation athletes show between competitions (;0.8%) (9,13,17). Previous studies have shown that an IMW (36) can improve intermittent run to exhaustion performance (Yo-Yo intermittent recovery test) in trained individuals by 19.5 6 12.6%.…”
Section: Discussionsupporting
confidence: 83%
“…On average, the IMW warm-up resulted in a ;21-second (2.8%) improvement in 3,200-m performance compared with CON. The effect is similar to those in comparable studies using a variety of performance tests (25,27,36,40), and greater than the smallest worthwhile change in performance athletes show between competitions, which is about half the typical variation athletes show between competitions (;0.8%) (9,13,17). Previous studies have shown that an IMW (36) can improve intermittent run to exhaustion performance (Yo-Yo intermittent recovery test) in trained individuals by 19.5 6 12.6%.…”
Section: Discussionsupporting
confidence: 83%
“…Specific to the focus of this paper, performance variability in athletics has received some research focus, primarily looking at intra-subject variability of 5 km time-trial running, 25 variability of performance between laboratory conditions and those simulating a real competitive event, 26 and within-athlete variation in performance. 27,28 Featuring prominently is the work of Hopkins and colleagues 2730 and the concept of the smallest worthwhile change (SWC).…”
Section: Introductionmentioning
confidence: 99%